Trophectoderm non-coding RNAs reflect the higher metabolic and more invasive properties of young maternal age blastocysts. (2nd January 2023) - Ntostis, Panagiotis; Swanson, Grace; Kokkali, Georgia; Iles, David; Huntriss, John; Pantou, Agni; Tzetis, Maria; Pantos, Konstantinos; Picton, Helen M.; Krawetz, Stephen A.; Miller, David
Abstract: Increasing female age is accompanied by a corresponding fall in her fertility. This decline is influenced by a variety of factors over an individual's life course including background genetics, local environment and diet. Studying both coding and non-coding RNAs of the embryo could aid our understanding of the causes and/or effects of the physiological processes accompanying the decline including the differential expression of sub-cellular biomarkers indicative of various diseases. The current study is a post-hoc analysis of the expression of trophectoderm RNA data derived from a previous high throughput study. Its main aim is to determine the characteristics and potential functionalities that characterize long non-coding RNAs. As reported previously, a maternal age-related component is potentially implicated in implantation success. Trophectoderm samples representing the full range of maternal reproductive ages were considered in relation to embryonic implantation potential, trophectoderm transcriptome dynamics and reproductive maternal age. The long non-coding RNA (lncRNA) biomarkers identified here are consistent with the activities of embryo-endometrial crosstalk, developmental competency and implantation and share common characteristics with markers of neoplasia/cancer invasion. Corresponding genes for expressed lncRNAs were more active in the blastocysts of younger women are associated with metabolic pathways including cholesterol biosynthesis and steroidogenesis.